Analyzing the challenges of music students through on-the-spot concert interviews in English learning - Denty Marga Sukma; Faricha Rizki (Journal of Educational Review and Research, 2026)
Extensive research has integrated music into the language learning context, yet few studies have examined how music students learn English as a Foreign Language (EFL) through the areas they are consistently immersed in on a daily basis as part of their college learning. This study addresses this gap by exploring how aligning language tasks with students' regular exposure to music can foster more authentic English learning. This aims to equip the students with the skills demanded in today’s fast-paced world, such as the growing importance of communication skills; thus, speaking skills in EFL are increasingly valued. The present study elaborates on how music-related activities were incorporated in EFL through on-the-spot concert interviews conducted by first-year music major students in higher education. This research utilized a qualitative method through a case study approach as an effort to gain a deeper understanding of how ELT can be integrated with real-time, on-the-spot concert interviews. The data were collected through document analysis and in-depth interviews. The findings allowed the students to expand their musical knowledge and simultaneously boost their confidence in speaking English. Moreover, the students' genuine interest in the concert experience led to vocabulary enrichment and spontaneous speaking enhancement during interviews, contributing positively to their speaking skill development. In conclusion, the project demonstrated that immersive, interest-driven activities can effectively enhance first-year music major students' speaking skills in English.